By design 2nd edition : why there are no locks on the bathroom doors in the hotel louis xiv and other object lessons - Caplan, Ralph ([S.l.] : Fairchild Books, 2004)
An inspiring resource for design students, professionals or anyone else who could benefit from a fuller appreciation of the design process, By Design vividly shows how design affects our most significant human activities. A network of engrossing stories illuminate the process as it applies to industrial design, interior design, fashion design, graphic design and the design of business and social situations. It is the perfect accompaniment to a broad area of foundation courses for designers-in-training. This new edition of the popular classic features updated examples of timeless ideas, illustrated in full colour. A concluding chapter discusses what has, and has not, changed since the first edition, examining design responses to radical technological development and shifting consumer demands. An elegant foreword by Paola Antonelli of the Museum of Modern Arts Department of Architecture and Design reintroduces the book to a fresh generation of readers.
Keywords: Industrial design